THE IMPORTANCE OF STUDENTS' INTELLECTUAL POTENTIAL IN RESEARCH - Rakhimov, Bakhtiyor Khudoyberdievich (SCIENCE and SOCIETY, 2026)
The issue of developing the intellectual potential of students in the organization of scientific research work has been the focus of psychologist scientists at all stages, the psychological features of the development of intelligence on scientific research in future teachers are scientifically theoretical. Considered a condition for the successful implementation of the activities of an individual, a scientific analysis has been carried out that the individual psychological characteristic manifested in the differences that arise in the dynamics of acquiring knowledge, skills and abilities are abilities.
Keywords: future teacher; intellect; intellectual development psychological process